Dietary addition of microencapsulated turmeric in an amorphous matrix of maltodextrin on quality characteristics of broiler chicken (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This experiment investigated the effect of microencapsulated turmeric by maltodextrin as an amorphous matrix material on the health status of broiler chickens. Materials and Methods: The broilers used were 144 healthy 1-day-old males. The average body weight was 47.8 ± 1.42 gm. The statistical design was based on a completely randomized design with four treatments and six replications. There were six broiler chickens in each experimental unit. The treatments were TM0 = 0 gm/kg of basal feed, TM1 = 1 gm/kg of basal feed, TM2 = 2 gm/kg of basal feed, and TM3 = 3 gm/kg of basal feed. The growth performance, physical traits, internal organs, microbial population, intestinal morphology, hematological parameters, and antioxidant profile were examined. Results: The results reported that microencapsulated turmeric by maltodextrin as an amorphous matrix significantly improved the hematological parameters, growth performance, antioxidant profile, LAB, immune organs, and intestinal morphology. The results also show decreasing coliform and pH of the cecum. Conclusions: Dietary addition of maltodextrin microencapsulated turmeric of 3 gm/kg in basal feed can be used as a natural feed additive to improve the health status of broiler chickens.J. Adv. Vet. Anim. Res., 9(2): 221–229, June 2022http://doi.org/10.5455/javar.2022.i587